Metabolomics analysis of human acute graft-versus-host disease reveals changes in host and microbiota-derived metabolites - David Michonneau (Nature Portfolio, 2019)
Graft versus host disease (GvHD) still hinders allogeneic hematopoietic stem cell transplantation. Here, the authors use metabolomics to analyze two cohorts of paired transplant recipients and donors, identifying significant differences in both host- and microbiota-derived metabolites.